UTILIZING BRAINLY AS A SOCIAL QUESTION-AND-ANSWER (Q&A) SERVICE IN ENGLISH LEARNING MATERIALS: BENEFITS AND LIMITATIONS - Fitria, Tira Nur (Journal of English Language and Culture, 2023)
This study describes Brainly as a social question-and-answer (Q&A) service in English learning and finds the positive and negative impacts on teachers and students. This research is descriptive qualitative. The analysis shows that using Brainly is easy. We can open Brainly at https://Brainly.co.id/. If we do not have an account, we can register using Gmail, then log in using the Brainly account. To make a question, click "Let's Ask", write down the questions, select the points to be rewarded to the answerers, choose the type of subject matter then click "Ask a Question". To answer a question, click the question to be answered in the "our answer" column fill in the answer, and click "Add Answer". Answering questions will add to our points. Based on previous studies, using Brainly have a positive and negative impact. Positively, teachers can convey concepts to their students simply and ability to connect students with education experts. Besides, students can add insight into knowledge which affects students' learning interests and learning outcomes. They can get answers and references and interact with each other to add answers or can be mutually correct. Brainly can provide easy content and is easily accessible to the student, this site is more practical compared to other educational sites, facilitate students in doing homework, can be used as an alternative to communicate virtually, and can be a learning resource and motivation simultaneously. Negatively, using Brainly creates students’ laziness to read books, reduces effectiveness in learning activities, generates dependency on Q&A technology, and familiarizes students to be passive to get an answer instantly. It impacts the teacher’s inability to control the students who used books or websites. However, further research certainly still needs to be done related to the level of accuracy of the answers given to the answerers on Brainly.